2019
DOI: 10.1098/rspa.2019.0468
|View full text |Cite
|
Sign up to set email alerts
|

Micro-structured medium with large isotropic negative thermal expansion

Abstract: A challenge in nano- and micro-mechanics is the realization of innovative materials exploiting auxetic behaviour to tailor thermal expansion properties. For this purpose, a new class of micro-structured media possessing an extremely wide range of tunable (positive, negative or even zero) thermal expansion is proposed and analytically and experimentally assessed. For this class of isotropic Mechanical-Auxetic Thermal-Shrinking media, the effective coefficient of thermal expansion is expl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 27 publications
0
10
0
Order By: Relevance
“…Alternative approaches to design auxetic media are presented in the reviews [28][29][30][31][32]. Some auxetic systems are also characterised by a negative value of the coefficient of thermal expansion, implying that they shrink when subjected to an increase in temperature [33][34][35]. Additionally, it has been shown that it is also possible to achieve a smooth transition through a wide range of negative and positive Poisson's ratios by using an origami cell that morphs continuously between a Miura mode and an eggbox mode [36][37][38].…”
Section: Introductionmentioning
confidence: 99%
“…Alternative approaches to design auxetic media are presented in the reviews [28][29][30][31][32]. Some auxetic systems are also characterised by a negative value of the coefficient of thermal expansion, implying that they shrink when subjected to an increase in temperature [33][34][35]. Additionally, it has been shown that it is also possible to achieve a smooth transition through a wide range of negative and positive Poisson's ratios by using an origami cell that morphs continuously between a Miura mode and an eggbox mode [36][37][38].…”
Section: Introductionmentioning
confidence: 99%
“…However, meta-materials exhibit extraordinary mechanical properties even when subject to quasi-static loading, particularly when large deformations are involved [19,20,21,22,23,24,25,26]. Examples are numerous, including cloaking [27], extreme stiffness [28], shape morphing [29], auxeticity [30,31], negative thermal expansion [32], and multistable architectures [33,34,35,36,37]. A flow in this research stream is the exploitation of structures beyond buckling and instability loads [38], in a range of extreme deformations [39].…”
Section: Introductionmentioning
confidence: 99%
“…However, metamaterials exhibit extraordinary mechanical properties even when subject to quasi-static loading, particularly when large deformations are involved [19][20][21][22][23][24][25][26]. Examples are numerous, including cloaking [27], extreme stiffness [28], shape morphing [29], auxeticity [30,31], negative thermal expansion [32] and multistable architectures [33][34][35][36][37]. A flow in this research stream is the exploitation of structures beyond buckling and instability loads [38], in a range of extreme deformations [39].…”
Section: Introductionmentioning
confidence: 99%